Evaluation of The Impacts of VMS on Traffic Performance Measures in An Urban Area in Indonesia - A. Caroline Sutandi (Civil Engineering Dimension, 2008)
Variable Message Sign (VMS) is especially recommended for congested flow conditions. The aim of this study is to investigate how drivers in a large city in a developing country with many specific geometric and traffic conditions and also specific driver behaviour, use VMS in aid of choosing route for their inter-city trips. Furthermore, to explore the impact of the use of the information on increasing traffic performance measures. A case study was carried out in Bandung, Indonesia. Microscopic traffic simulations were used in this study to evaluate traffic performance measures. The results of the evaluation found that VMS has insignificant impact on driversâ route choice behaviour. The results indicated that drivers in Bandung rely much on their experience of traffic conditions commonly occur in the city and demonstrated that VMS has no significant impact to increase traffic performance, but has better impact on the roads with higher number of alternative roads.